Review on Public Long-Term Care Services for Older People in Malaysia - Muhammad Safwan Hamdy; Mazlynda Md Yusuf (Universiti Sains Islam Malaysia, 2024)
Long term care is initially known for its traditional way in providingelderly careservice in family-and relative-dependence society. Advancing from that point, public long-term care services beginin Malaysia by the government and this emerges into a higher demand industry with private service provision.Long-term care components include healthcare, accommodation, meals, daily tasks assistance and others, the facilitiesand caregiving services are expected to cover those components comprehensively. Previous researches extensively reviewed the available facilities, but less is done on classifying these facilities according to benefit types of services. This paper discusses the function and facilities available under Malaysia's Department of Social Welfare particularly in the long term care aspect for their elders. Further discussion is done on how these available facilities engage the long-term care need for Malaysian elderly based on Activity of Daily Living (ADL) and Instrumental Activity of Daily Living (IADL) categories. From cash and in-kind benefits, home and institutional care, the paper is expected to explore how they are functioning accordingly as compared to othercountries, in accordance to the need of long term care for the elders in Malaysia.